Program Pendampingan Menulis “Surat untuk Allah” Berbasis Pengalaman Religius Pribadi di TPA Manarul Huda Tanjung Baru Timur - M, Marleni; Mutiara, Yolanda; W, Wantika; andayani, Amelia H (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service program assisted 15 children of Taman Pendidikan Al-Qur’an Manarul Huda, Tanjung Baru Timur, North Lampung (aged 7–12 years) in writing “Letters to Allah” containing their personal religious experiences and heartfelt confessions. The solution or implementation method was carried out simply on 22 November 2025 for 90 minutes through several stages: introduction to the concept of personal religious experience using a short story about Al-Ghazali and William James, distribution of coloured paper and cute envelopes, guided free writing, voluntary reading of the letters, and storage of the letters in a special “Mailbox for Allah” placed permanently in the TPA premises. The service successfully produced 12 original and deeply touching letters written by the children. The observed impacts included increased courage among the children to express their religious feelings, greater enthusiasm for Qur’anic studies, and reports from TPA administrators that the children more frequently talked about Allah at home. The outputs obtained were a permanent mailbox in the TPA, a digital photo album containing all the children’s letters, and a simple implementation guide document that can be easily replicated by other TPAs without significant cost.